2016
DOI: 10.1039/c6py01343k
|View full text |Cite
|
Sign up to set email alerts
|

Group interval-controlled polymers: an example of epoxy functional polymers via step-growth thiol–yne polymerization

Abstract: Here, we successfully synthesized a series of epoxy GICPs via one-step UV-triggered thiol–yne polymerization of commercial glycidyl propargyl ether and dithiols at 0 °C..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…These results were in good agreement with the observed thiol‐yne polymerization of 1 and another alkynyl monomer ( M n = 2400 g mol −1 and PDI = 1.42) . In addition, the GPC curves were unimodal, which further confirmed that no side reactions occurred among thiol and epoxy groups and no coupling termination events were involved in the process of chain growth because of the ultrahigh chain transfer constant of thiol monomers (Scheme S2 and Figure S2, Supporting Information) …”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…These results were in good agreement with the observed thiol‐yne polymerization of 1 and another alkynyl monomer ( M n = 2400 g mol −1 and PDI = 1.42) . In addition, the GPC curves were unimodal, which further confirmed that no side reactions occurred among thiol and epoxy groups and no coupling termination events were involved in the process of chain growth because of the ultrahigh chain transfer constant of thiol monomers (Scheme S2 and Figure S2, Supporting Information) …”
Section: Resultsmentioning
confidence: 60%
“…For the achieved P1 , the T d5 (thermal decomposition temperature at 5 wt% loss) was 211.5 °C, the T d (decomposing temperature) was 307.8 °C, and the T d max (maximum decomposing temperature) was 340.7 °C. The T d of the P1 was slightly higher than those (about 295 °C) of the epoxy–containing polythioethers synthesized by UV‐initiated thiol‐yne click polymerization of the alkyl‐based dithiol compounds and propargyl glycidyl ether …”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations